2017
DOI: 10.1038/ncomms15019
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous adenosine maintains cartilage homeostasis and exogenous adenosine inhibits osteoarthritis progression

Abstract: Osteoarthritis (OA) is characterized by cartilage destruction and chondrocytes have a central role in this process. With age and inflammation chondrocytes have reduced capacity to synthesize and maintain ATP, a molecule important for cartilage homeostasis. Here we show that concentrations of ATP and adenosine, its metabolite, fall after treatment of mouse chondrocytes and rat tibia explants with IL-1β, an inflammatory mediator thought to participate in OA pathogenesis. Mice lacking A2A adenosine receptor (A2AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
153
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(179 citation statements)
references
References 68 publications
11
153
0
1
Order By: Relevance
“…Despite the increased level of NTPDases expression in chondrogenically induced MSCs, the activity of these enzymes toward ATP remains quite low. This is in agreement with the latest study on NTPD1 knock-out mice that did not suffer from decreased ATP hydrolysis and Ado production (Corciulo et al, 2017). Supported by literature data, we hypothesize that structure-function relationships in chondrogenic lineage dictate the direction of nucleotides metabolism.…”
Section: Chondrogenic Differentiationsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite the increased level of NTPDases expression in chondrogenically induced MSCs, the activity of these enzymes toward ATP remains quite low. This is in agreement with the latest study on NTPD1 knock-out mice that did not suffer from decreased ATP hydrolysis and Ado production (Corciulo et al, 2017). Supported by literature data, we hypothesize that structure-function relationships in chondrogenic lineage dictate the direction of nucleotides metabolism.…”
Section: Chondrogenic Differentiationsupporting
confidence: 93%
“…Furthermore, digoxin and ATP increased the tensile modulus by 280% and 180%, respectively, and the application of both agents enhanced it by 380%. Considering the regulatory role of Ado in the cartilage, the A2A receptor agonists have been recently claimed to be a promising target for the treatment of OA since mice lacking the A2A receptors spontaneously develop the disease (Corciulo et al, ).…”
Section: Differentiation Of Mscsmentioning
confidence: 99%
“…the pathogenesis of OA by inducing the chondrocyte anabolic and catabolic imbalance, including the downregulation of Collagen II and Aggrecan, as well as the upregulation of ADAMTS-5 and MMP-13 [45][46][47]. Therefore, we treated chondrocytes with IL-1b to simulate the OA microenvironment in vitro, similar to other studies [10,48]. When chondrocytes were exposed to IL-1b, we observed the same SGK1 expression pattern as detected in OA cartilage.…”
Section: Discussionsupporting
confidence: 72%
“…Among these pro‐inflammatory cytokines, increased IL‐1β levels have consistently been observed in the cartilage tissue, synovial fluid and the blood of patients with OA , and it plays a critical role in the pathogenesis of OA by inducing the chondrocyte anabolic and catabolic imbalance, including the downregulation of Collagen II and Aggrecan, as well as the upregulation of ADAMTS‐5 and MMP‐13 . Therefore, we treated chondrocytes with IL‐1β to simulate the OA microenvironment in vitro , similar to other studies . When chondrocytes were exposed to IL‐1β, we observed the same SGK1 expression pattern as detected in OA cartilage.…”
Section: Discussionsupporting
confidence: 69%
“…Adenosine signaling via the P1 receptor family of G protein-coupled receptors plays a key role in bone formation and homeostasis [52,53]. Recently, emerging studies have shown that adenosine signaling also plays a key role in regulating chondrocyte function and cartilage homeostasis [54,55]. Taken together, the single-unit scaffold may have provided a combination of chemical and structural cues that support osteochondral tissue formation.…”
Section: Discussionmentioning
confidence: 99%